Batik SMEs In East Java Indonesia: Interrelationship Between Personal Value and Management Skills Towards SMEs Performance in The New Normal Era - Murtianingsih Murtianingsih; Ubud Salim; Atim Djazuli; Sudjatno Sudjatno (Research Synergy Foundation, 2021)
The development of Batik SMEs in East Java shows a sector that is highly affected by the pandemic due to the unpreparedness of SMEs to face the pandemic conditions. The need for encouragement from the government and strengthening this sector so that it can develop again and make a positive contribution to the regional and national economy. Managerial aspects and personal values owned by Batik SMEs in East Java are expected to be a reinforcing factor for SMEs in facing a very dynamic environment. The purpose of this study was to determine the relationship between personal values and management skills on the performance of Batik SMEs during the new normal era in East Java, Indonesia. The data used were obtained through a survey using a questionnaire, which was then analyzed by factor analysis, descriptive statistics, Pearson product-moment correlation, and multiple regression. The results of the study stated that there was no relationship between personal values and performance, and there was no relationship between management skills and the performance of Batik SMEs in East Java, Indonesia. This research does not include external factors of the research variables, namely government policies that can be measured by inflation rates and tax policies, as well as Bank Indonesia credit interest rates. This study uses the variable management skills, personal values, and performance of Batik SMEs in East Java during the normal era, which are products with local cultural features.